2018
DOI: 10.1016/j.newast.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Rotational and X-ray luminosity evolution of high-B radio pulsars

Abstract: In continuation of our earlier work on the long-term evolution of the so-called high--B radio pulsars (HBRPs) with measured braking indices, we have investigated the long-term evolution of the remaining five HBRPs for which braking indices have not been measured yet. This completes our source-by-source analyses of HBRPs in the fallback disc model that was also applied earlier to anomalous X-ray pulsars (AXPs), soft gamma repeaters (SGRs), and dim isolated neutron stars (XDINs). Our results show that the X-ray … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…The estimated B0,min values seen in Fig. 2 is important in that it is compatible with a continuous distribution for the B0 values of all single neutron star populations (AXP/SGR, XDIN, HBRP, RRAT and CCO) in the fallback disc model, filling the gap between B0 ∼ 10 9 G for CCOs (Benli & Ertan 2018a) and B0 10 11 G for the other populations (Alpar 2001;Ekşi & Alpar 2003;Ertan et al 2007Ertan et al , 2009Ertan et al , 2014Ertan 2017;Benli & Ertan 2017, 2018b.…”
Section: The Model and Application To Rrat J1819-1458supporting
confidence: 66%
See 2 more Smart Citations
“…The estimated B0,min values seen in Fig. 2 is important in that it is compatible with a continuous distribution for the B0 values of all single neutron star populations (AXP/SGR, XDIN, HBRP, RRAT and CCO) in the fallback disc model, filling the gap between B0 ∼ 10 9 G for CCOs (Benli & Ertan 2018a) and B0 10 11 G for the other populations (Alpar 2001;Ekşi & Alpar 2003;Ertan et al 2007Ertan et al , 2009Ertan et al , 2014Ertan 2017;Benli & Ertan 2017, 2018b.…”
Section: The Model and Application To Rrat J1819-1458supporting
confidence: 66%
“…To test these ideas, a long-term evolution model for neutron stars with fallback discs was developed including the effects of X-ray irradiation with contribution of the intrinsic cooling of the neutron star, and the inactivation of the disc at low temperatures on the evolution of the star (Ertan et al 2009;Alpar et al 2011;Çalışkan et al 2013). Later, it was shown that the individual source properties of AXP/SGRs (Benli & Ertan 2016), XDINs (Ertan et al 2014, high magnetic-field radio pulsars (HBRPs) (Çalışkan et al 2013;Benli & Ertan 2017, 2018b, and CCOs (Benli & Ertan 2018a) can be reproduced in the same long-term evolution model with very similar main disc parameters, supporting the idea proposed by Alpar (2001).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…In the fallback disc model, B 0 values are estimated to be one to three orders smaller than the values inferred from the dipole torque formula. The long-term evolution of XDINs and HBRPs with fallback discs was studied earlier by Ertan et al (2014) and Benli & Ertan (2017, 2018a. The model can reproduce P, P and L x of individual XDIN and HBRP sources with B 0 in the ranges of (0.3 -1.3) ×10 12 G for XDINs and (0.3 -6) × 10 12 G for HBRPs.…”
Section: Introductionmentioning
confidence: 90%
“…The model can reproduce P, P and L x of individual XDIN and HBRP sources with B 0 in the ranges of (0.3 -1.3) ×10 12 G for XDINs and (0.3 -6) × 10 12 G for HBRPs. These relatively weak fields together with the long periods place XDINs well below the pulsar death line (see Ertan et al 2014, figure 4) in the B 0 − P diagram (Chen & Ruderman 1993), while HBRPs with relatively strong fields and/or short periods are located above the death line (Benli & Ertan 2017, 2018a. In other words, in the fallback disc model, the lack of radio pulses from XDINs is due to their weak dipole fields, rather than the beaming geometry.…”
Section: Introductionmentioning
confidence: 96%